"Smithsonian Institution, Washington" - Archiwum Biblioteki Kórnickiej (1869-1923); Biblioteka Kórnicka; Smithsonian Institution (Waszyngton) (1856)
1. "List of works published by the Smithsonian Institution, january 1857", k. 33.
29 listów
Keywords: Lwów; Zakład Narodowy im. Ossolińskich; Waszyngton; Smithsonian Institution; Korespondencja